2016
DOI: 10.1177/0269881116668593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a single, oral 60 mg caffeine dose on attention in healthy adult subjects

Abstract: Caffeine induces positive effects on sustained attention, although studies assessing the acute effects of low caffeine dose (<75 mg) on sustained attention are limited and use short-term tests. Therefore, we investigated the acute effects of a 60 mg dose of caffeine on sustained attention in tests lasting up to 45 minutes using 82 low or non-caffeine-consuming healthy male ( n=41) and female ( n=41) adults aged between 40 and 60 years. Vigilance was measured using Mackworth Clock test, Rapid Visual Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…All participants received antidepressant escitalopram medication for 2 to 3 wk before enrollment. The dose of caffeine was selected according to previous finding that consumption of low dose of caffeine (60 mg) induced significant improved cognition and positive mood . The participants included in the current investigation were not regular caffeine drinkers before enrollment and the heavy caffeine users (more than 3 cups/ day) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…All participants received antidepressant escitalopram medication for 2 to 3 wk before enrollment. The dose of caffeine was selected according to previous finding that consumption of low dose of caffeine (60 mg) induced significant improved cognition and positive mood . The participants included in the current investigation were not regular caffeine drinkers before enrollment and the heavy caffeine users (more than 3 cups/ day) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed they found that caffeine maintained vigilance and improved running performance during an overnight field operation in these soldiers [23]. Another investigation found that in healthy adult subjects, the acute consumption of 60 mg of caffeine improved sustained attention and alertness [24]. It should be noted that the dose of caffeine in the current study was 300 mg or approximately four mg of caffeine per kilogram of body weight.…”
Section: Discussionmentioning
confidence: 63%
“…since the 1920s [22]. Today it can be used independently or as a supplement to other measurements and may be used even in pharmacology [23]. The scale consists of a line that is usually 100 mm in length.…”
Section: The Visual Analogue Scale (Vas)mentioning
confidence: 99%